Economic Freedom, Investment Flexibility, and Equity Value: A Cross-Country Study - CHEN, Chih-Ying (Institutional Knowledge at Singapore Management University, 2015)
Prior studies show that equity value has convex relations with earnings and book value of equity, respectively, due to growth and adaptation options (Burgstahler and Dichev 1997a; Zhang 2000). These studies, however, do not consider the role of institutions in affecting firms' ability to exercise growth and adaptation options. In this study, we investigate whether these convex relations vary with the degree of a country's economic freedom, which may influence the frictions and costs of exercising these options. We develop four hypotheses: In countries with greater economic freedom, (1) a firm's capital investment in response to profitability is greater; (2) the relation between equity value and earnings, given equity book value, is more convex; (3) the relation between equity value and equity book value, given earnings, is more convex; and (4) the relation between stock return and profitability change is more convex. Using the index of economic freedom from the Fraser Institute, we test our hypotheses with data from 30 countries during the 2000-2010 period. The empirical results are consistent with these hypotheses. The effect of economic freedom that we document is distinct from the effects of GDP level and growth, legal origin, law enforcement, investor protection, and quality of accounting standards. Our results suggest that greater economic freedom enhances equity value through more efficient management of investment options.